Performance of Sorghum to Different Doses of Npk Fertilizer - Puji Harsono (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2017)
Sorghum (Sorghum bicolor L., Moench) stover demonstrated to be a potential biomass energy source. Sorghum is an important cereal commodity that being uses as food, forage, industry. A renewable energy or biofuel of sorghum (ethanol) could be extracted from the steam of sorghum. Field experiment was conducted at Sukoharjo, Central Java from April to June, 2015. An experiment of several doses of NPK fertilizer was aimed to get optimal biomass of sorghum in different doses NPK fertilizer application, with three replication was apllied to evaluate five doses NPK fertilizer (0, 40,60, 80, 100 and 120) kg.ha-1 . The data was subjected to an analysis of variance followed by BNT. The result showed that the plants treated with 60 kg.ha-1 increase plant height at 60 days after planting, biomass per plot and weight of seed per plant.Key words: sorghum, fertilizer, variety and biomass.